GROSS EMPLOYMENT OF THE POPULATION IN THE REPUBLIC OF UZBEKISTAN (International journal of artificial intelligence, 2025)
This article explores the total employment of the population in the Republic of Uzbekistan, analyzing its structure, trends, and socio-economic implications. Total employment reflects the proportion of the working-age population engaged in economic activities, serving as a key indicator of labor market health and overall economic development. The article examines the dynamics of employment across sectors, regional disparities, and factors influencing labor participation, such as education, demographic changes, and government policies. Additionally, the study highlights challenges related to underemployment, informal work, and the need for sustainable job creation. The findings contribute to understanding labor market trends in Uzbekistan and provide a foundation for evidence-based economic and social policy planning.